The Influence of Communication and Work Culture on Work Motivation and Its Impact on Work Performance at the Public Works Department of Bengkalis Regency - Al Ucok, Imran; Siswanto, Didik; Munthe, Richa Afriana (Lembaga Riset dan Inovasi Al-Matani, 2024)
The purpose of this study is to examine the influence of communication and work culture on work motivation and its impact on work performance at the Public Works Department of Bengkalis Regency. This research employs a descriptive quantitative approach and was conducted from October 2017 to December 2017. The study sample consists of 97 employees from the Public Works Department of Bengkalis Regency who participated in interviews. The data analysis methods used in this study include path analysis, normality test, linearity test, goodness-of-fit test, and hypothesis testing. The findings reveal that communication and work culture have a significant effect on employees' work motivation at the Public Works Department of Bengkalis Regency. Additionally, communication and work motivation significantly influence employees' work performance. However, work culture does not directly affect employees' work performance. Furthermore, the study confirms that communication and work culture have a significant effect on work performance through work motivation.